2000
DOI: 10.1128/jcm.38.4.1385-1389.2000
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Enzyme Immunoassay for Determination of Toxigenicity among Clinical Isolates of Corynebacteria

Abstract: A rapid enzyme immunoassay (EIA) was developed for the phenotypic detection of diphtheria toxin among clinical isolates of corynebacteria. The assay uses equine polyclonal antitoxin as the capture antibody and an alkaline phosphatase-labeled monoclonal antibody, specific for fragment A of the toxin molecule, as the detecting antibody. The assay is rapid, sensitive, and specific: a final result is available within 3 h of colony selection, and the limits of detection are 0.1 ng of pure diphtheria toxin/ml. Toxig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 24 publications
0
8
0
Order By: Relevance
“…29 Enzyme Immunoassay (EIA), using monoclonal antibody to fragment A of the exotoxin, is highly accurate and could improve diagnosis in false-negative the Elek and RT-PCR test. 30 Since the differential diagnosis of malignant skin lesions such as squamous cell carcinoma (SCC) should be considered for non-healing chronic ulcers, the histopathologic examination is encouraged for definite diagnosis and rule outing non-infectious etiologies.…”
Section: Discussionmentioning
confidence: 99%
“…29 Enzyme Immunoassay (EIA), using monoclonal antibody to fragment A of the exotoxin, is highly accurate and could improve diagnosis in false-negative the Elek and RT-PCR test. 30 Since the differential diagnosis of malignant skin lesions such as squamous cell carcinoma (SCC) should be considered for non-healing chronic ulcers, the histopathologic examination is encouraged for definite diagnosis and rule outing non-infectious etiologies.…”
Section: Discussionmentioning
confidence: 99%
“…ELISA testing was performed between February 2021 and January 2022. For ELISA testing bacterial strains were cultured on Elek broth [ 6 , 7 ] for 6 h at 37 °C, after which the bacterial cells were removed by filtration through a 0.22-µm-pore-size membrane (Merck Millipore, Burlington, MA, USA). The culture supernatants were stored at −20 °C prior to analysis in the ELISA.…”
Section: Methodsmentioning
confidence: 99%
“…ELISA remains a very robust and reliable method for the detection of various protein analytes. Previously, enzyme-linked immunosorbent and immunochromatographic methods for detecting DT were developed, the sensitivity of which varied from 0.1 to 4 ng/mL [ 5 , 6 , 7 ]. These tests were based on a sandwich immunoassay with equine polyclonal antibodies as binding antibodies, and mouse monoclonal antibodies (mAbs) as detecting antibodies.…”
Section: Introductionmentioning
confidence: 99%
“…EIA is also characterised by a very high diagnostic sensitivity (LOD is 0.1 ng/mL). In a comparative study of 220 toxigenic Corynebacterium isolates, the results obtained by the EIA method correlate 100% with the results obtained by the Elek test [ 51 ]. Engler et al also reported 100% consistency of the results of both methods [ 51 ].…”
Section: Immunological Assaysmentioning
confidence: 99%